2015
DOI: 10.1038/tpj.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9, CYP2C19, ABCB1 genetic polymorphisms and phenytoin plasma concentrations in Mexican-Mestizo patients with epilepsy

Abstract: We aimed to explore the possible influence of CYP2C9 (*2, *3 and IVS8-109 A>T), CYP2C19 (*2, *3 and *17) and ABCB1 (1236C>T, 2677G>A/T and 3435C>T) on phenytoin (PHT) plasma concentrations in 64 Mexican Mestizo (MM) patients with epilepsy currently treated with PHT in mono- (n=25) and polytherapy (n=39). Genotype and allele frequencies of these variants were also estimated in 300 MM healthy volunteers. Linear regression models were used to assess associations between the dependent variables (PHT plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…A statistical comparison revealed that the frequency of CYP2C9*1 / *2 was, overall, 50% lower amongst patients with DMT2 compared with healthy individuals (6.5 vs. 9-16%; P<0.05) (data not shown) (42-45), whereas CYP2C9*2/*2 was 40% lower amongst the patients with DMT2 compared with healthy volunteers from northern Mexico (0.04 vs. 1.0%; P<0.05) (data not shown) (42-45). CYP2C9*1 / *3 was significantly different only amongst populations from Sonora, Mexico City and Guerrero (5 vs. 10%, 1% and 10%; P<0.05) (29,42-46) (data not shown).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…A statistical comparison revealed that the frequency of CYP2C9*1 / *2 was, overall, 50% lower amongst patients with DMT2 compared with healthy individuals (6.5 vs. 9-16%; P<0.05) (data not shown) (42-45), whereas CYP2C9*2/*2 was 40% lower amongst the patients with DMT2 compared with healthy volunteers from northern Mexico (0.04 vs. 1.0%; P<0.05) (data not shown) (42-45). CYP2C9*1 / *3 was significantly different only amongst populations from Sonora, Mexico City and Guerrero (5 vs. 10%, 1% and 10%; P<0.05) (29,42-46) (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…IVS8-109T has already been observed amongst healthy volunteers, where it displays substantial interethnic variability (25). When comparing IVS8-109A>T variants from the studied Mexican patients with DMT2 with healthy individuals from different countries, including Sweden (25), Japan (46), Korea (25,47), Ecuador (26) and Mexico (29) itself, statistically significant differences were identified regarding the frequencies of A / T and T / T , and the prevalence of the alleles A and T in every case (P<0.05; Table V).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…To complicate the matter further, the same intronic SNP has now been reported to lead to decreased metabolic activity towards phenytoin in Mexican Mestizo patients with epilepsy. 72 One study recently reported that a common variant of P450 Oxidoreductase gene ( POR*28 ) was associated with altered CYP2C9 activity in Swedish, but not Korean, healthy subjects. 73 Its impact was determined to be only minimal in a Spanish population.…”
Section: Ethnicity and Variant Alleles Controlling Drug Metabolismmentioning
confidence: 99%